2020
DOI: 10.1002/ana.25969
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of the max‐ICH Score in Intracerebral Hemorrhage

Abstract: Objective Outcome prognostication unbiased by early care limitations (ECL) is essential for guiding treatment in patients presenting with intracerebral hemorrhage (ICH). The aim of this study was to determine whether the max‐ICH (maximally treated ICH) Score provides improved and clinically useful prognostic estimation of functional long‐term outcomes after ICH. Methods This multicenter validation study compared the prognostication of the max‐ICH Score versus the ICH Score regarding diagnostic accuracy (discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
0
28
1
Order By: Relevance
“…With the exception of the max-ICH score, which was fully validated recently, none of the scores identified in our literature search provided complete score validation [ 29 ]. Here we chose the Essen-ICH-score to illustrate the three methodological pillars of validation discrimination, calibration, and net benefit analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the max-ICH score, which was fully validated recently, none of the scores identified in our literature search provided complete score validation [ 29 ]. Here we chose the Essen-ICH-score to illustrate the three methodological pillars of validation discrimination, calibration, and net benefit analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the 583 patients included in the study conventional prognostication overestimated the observed mortality by 45% and overestimated the observed unfavorable outcome by 10% [ 27 ]. The max-ICH score is the only score that we are aware of that has been fully validated according to the criteria laid out in this review [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 6 Moreover, prolonged impairment of consciousness may result in unjustified care limitation and worse patient outcome by selffulfilling prophecy. [7][8][9][10] Amantadine, an N-methyl-D-aspartate receptor antagonist and indirect dopamine agonist, exerts effects on multiple neurotransmitters and is used as neurostimulant in patients with prolonged disorders of consciousness. 11 12 A randomised controlled trial and several observational studies showed that amantadine accelerated functional recovery in TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction scores used in the acute phase have limited accuracy for the prediction of 30-day mortality and functional outcome, 19 23 and appear especially unreliable for the higher scores that predict poor outcome. 24 Furthermore, these prediction scores do not facilitate physicians in their choice for a certain treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Current guidelines recommend hyperosmotic therapy if a patient has acute elevated intracranial pressure with signs of herniation, but advice against the use of glucocorticoids. 10,11,17,18 Prediction scores used in the acute phase have limited accuracy for the prediction of 30-day mortality and functional outcome, [19][20][21][22][23] and appear especially unreliable for the higher scores that predict poor outcome. 24 Furthermore, these prediction scores do not facilitate physicians in their choice for a certain treatment strategy.…”
Section: Introductionmentioning
confidence: 99%